Analisis Hubungan antara Self-Efficacy dan Persepsi Mahasiswa terhadap Strategi Problem Solving dalam Konteks Literasi Matematika - Sakarti, Hanuri (Papanda, 2025)
This study aims to analyze the relationship between self-efficacy and students' perceptions of problem-solving strategies within the context of mathematical literacy. Using a quantitative correlational approach, this research involved 20 students selected through purposive sampling. Data were collected using two Likert scale questionnaires to measure self-efficacy and perceptions of problem-solving strategies. As the data were not normally distributed based on the Shapiro-Wilk test (p < 0.05), the relationship was analyzed using the Spearman correlation test. The results showed a correlation coefficient (rₛ) of 0.293 with a significance value (p-value) of 0.210. Since the p-value > 0.05, it is concluded that there is no statistically significant relationship between self-efficacy and students' perceptions of problem-solving strategies. Although a weak positive trend was observed, the null hypothesis stating no significant relationship could not be rejected in this study.